Image Retrieval: Challenges and Solutions - Martínez Comeche, Juan Antonio (Revista General de Información y Documentación, 2013)
Analysis of the peculiar characteristics of images as documents and its consequences for the development of automated retrieval of this type of documentation. After developing the concepts of image and image retrieval, the challenges that image presents from the point of view of retrieval are analyzed, especially the semantic gap, and the main solutions found in the literature since 1990 to present are described. The current approach (SBVIR) is characterized by the simultaneous employment of the visual code and the language in representing images.